Patterns of change in physical functioning and posttraumatic stress disorder with cognitive processing therapy in a randomized controlled implementation trial. Issue 1 (31st December 2020) - Song, Jiyoung; Johnson, Clara; Suvak, Michael K.; Shields, Norman; Lane, Jeanine E. M.; Monson, Candice M.; Wiltsey-Stirman, Shannon
ABSTRACT: Background : Physical health concerns (e.g. chronic pain, fatigue) are common among clients with posttraumatic stress disorder (PTSD). Prior research has indicated that clients report improved physical functioning and fewer physical health symptoms after receiving Cognitive Processing Therapy (CPT) for PTSD. However, less is known about the impact of physical functioning on the clients' PTSD symptom improvement in CPT. Objective : The current study examined the patterns of change of and between physical functioning and PTSD symptoms over the course of CPT among a diverse military, veteran, and community sample. Method : We collected clients' ( N = 188) physical functioning and PTSD symptom severity prior to and during CPT using the 12-Item Short Form Health Survey and the PTSD Checklist. We used multilevel modelling to 1) evaluate the impact of baseline physical functioning on the PTSD symptom trajectory, 2) examine the trajectory of physical functioning, and 3) assess the dynamics between physical functioning and PTSD symptoms over the course of CPT. Results : Our multilevel analyses indicated that 1) physical functioning significantly improved for those with low levels of functioning prior to treatment, 2) poorer baseline physical functioning predicted slower improvements in PTSD symptoms, and 3) poorer physical functioning in one session predicted less PTSD symptom improvement by the next session. Conclusions : Our findings demonstrate that while physical functioning can interfere with PTSD symptom improvement, physical functioning can also improve over the course of CPT. In light of the interconnected nature of physical health and PTSD symptoms, clinicians may need to attend to lower levels of physical functioning when providing CPT or other trauma-focused therapies. Future research to determine whether specific treatment adaptations may benefit such clients is needed.